Investigating the pedagogies of screen‐sharing in contemporary learning environments—A mixed methods analysis. (8th February 2022) - Stevenson, Michael; Lai, Jennifer W. M.; Bower, Matt
Abstract: Background: Screen‐sharing technologies enable applications such as screen mirroring, video streaming and instant messaging across multiple device screens. Despite their increasing use in many contemporary classrooms, there is a paucity of research directly examining pedagogical benefits and issues of these technologies. Objectives: This study investigated the influence of screen‐sharing technologies on teachers' practices, highlighting pedagogical benefits and issues encountered. Methods: The paper drew on a sample of 321 K‐12 teachers and utilised principal components analysis, descriptive statistics and inductive coding. Results and Conclusions: Teachers reported greater mobility, increased ease of content sharing and deeper learner cognition as attributes of improved learning and teaching with the technologies. However, a minority highlighted technical issues such as network and hardware problems affecting their confidence. Despite increased mobility as an affordance, teachers' perceptions about mobility largely appeared to be predicated on assumptions that the technologies were intended for didactic instruction. Takeaways: The study contributes to a more nuanced understanding of screen‐sharing affordances while underscoring learner‐led screensharing as a focus for future research and practice. Lay Description: What is already known about this topic: Screen‐sharing technologies are becoming commonplace in many contemporary educational settings. The technologies represent integrated systems that enable functions such as mirroring, video streaming, online polls, real‐time editing, screen‐capturing and learner analytics. Screen‐sharing is indirectly examined in several studies with findings indicating improvements in group awareness, emotional engagement, learner confidence to share ideas and teachers' visualization of concepts. Existing findings are largely anecdotal and there are very few studies that have focused directly on screen‐sharing affordances. What this paper adds: An empirical study directly examining teachers' first‐hand perspectives of using screen‐sharing technologies. Benefits relate to greater task focus, deeper thinking, improvements to teaching practice and ease of sharing content. A minority of teachers experienced issues such as technical problems, inappropriate sharing and distraction. Mobility was recognized as a key affordance though remained underutilized by many teachers. Implications for practice and/or policy: Professional learning accompanying the use of screen‐sharing technologies can support teachers to take advantage of all features of screen sharing such as enhanced teacher mobility. Institutions need to provide requisite technical and professional support for teachers to effectively and reliably leverage screen‐sharing in the classroom. There is a need to explore teacher's and learner's screen‐sharing uses in situ to more fully understand issues and possibilities.